2021
DOI: 10.3892/etm.2021.10862
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum assessment of fetal inflammatory response syndrome in a preterm population with premature rupture of membranes: A Romanian study

Abstract: Fetal inflammatory response syndrome is associated with increased neonatal morbidity and mortality. The aim of the present study was to evaluate the dynamics of the plasmatic value of pro-inflammatory cytokines: tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and neutrophil activating peptide 78 (ENA-78) and the anti-inflammatory cytokine IL-10 in the first and third day of life and the correlation with neonatal morbidities and mortality. The current research was designed as a prospective case control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…In neonates born to mothers with PROM, NEC may be associated with an exaggerated inflammatory response involving the release of cytokines and chemokines, which can cause intestinal mucosal injury. A prospective case-control study has demonstrated elevated levels of IL-6, IL-10, and ENA-78 in the venous blood of newborns from mothers with PROM compared to normal controls ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In neonates born to mothers with PROM, NEC may be associated with an exaggerated inflammatory response involving the release of cytokines and chemokines, which can cause intestinal mucosal injury. A prospective case-control study has demonstrated elevated levels of IL-6, IL-10, and ENA-78 in the venous blood of newborns from mothers with PROM compared to normal controls ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Руйнування існуючих нейронів або втручання у міграцію або розвиток нових нейронів призводить до аберантного розвитку кори, аномального розвитку мозку з подальшими когнітивними та поведінковими порушеннями. Наявність незрілих олігодендроцитів і амебоїдної мікроглії в ділянці білої речовини мозку у кінці ІІ триместра може зумовити підвищену вразливість мозку до будь-яких патологічних процесів [20,21].…”
Section: синдром системной воспалительной реакции плода (клиническая ...unclassified